Konfirmasi Stunting dan Skrining Weight faltering pada Baduta - Fairuza, Firda; Setiati, Dita; Ningrum, Nathalia; Ferdi Fadilah, Tubagus; Sari, Meiriani; Aziza, Nia Nurul (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Community service activities were carried out in the form of confirming stunting in infants under two years old and health screening for weight faltering infants under two years old in Kelurahan Jati Pulo to improve the health and nutritional status of children in one of the work areas of the West Jakarta Health sub-department. The location for the activity was chosen because the sub-district is one of the sub-districts with the most stunting findings and was located close to the Trisakti University. The stunting screening for children under five in the work area of the primary health care follows the National Guidelines for Health Services for stunting in primary healthcare facilities. Still, apart from anthropometric examinations, the diagnosis of stunting was made based on anamnesis, physical examination and supporting examinations carried out by a pediatrician. The purpose of this service activity was to confirm stunting in under-fives and prevent stunting by screening children's weight-faltering health to optimize the nutritional status and health of toddlers so that parents can provide good and proper care for the process of growth and development of children to prevent health and nutrition problems in toddlers. The benefit of this activity was that parents, especially mothers of toddlers, know their children's nutritional status and the importance of the First 1000 Days of Life to prevent nutritional problems in toddlers and improve children's health and nutritional status.